Sistem Pendukung Keputusan Pemilihan Debt Collector Berprestasi Di PT. Wahana Ottomitra Multiartha Medan Menerapkan Metode SMARTER - Gulo, Dewi Hartati (CV. Graha Mitra Edukasi, 2023)
An outstanding debt collector must have presence, honesty, teamwork and achievement to improve the debt collector's performance. Problems in selecting outstanding debt collectors at PT. Wahana Ottomitra Multiartha Medan is an election team that finds it difficult to carry out elections quickly and accurately. The decision making technique in the SMARTER (Simple Multi-Attribute Rating Technique Exploiting Ranks) method is based on the theory that each alternative consists of a number of criteria that have values ​​and each criterion has a weight that describes how important it is compared to other criteria. Application of the Simple Multi-Attribute Rating Technique Exploiting Rank method for selecting outstanding debt collectors at PT. Wahana Ottomitra Multiartha Medan provides an accuracy of 23% using the relative standard deviation formula. It is hoped that to overcome this, a Decision Support System for Selection of Outstanding Debt Collectors at PT was built. Wahana Ottomitra Multiartha Medan Implements the SMARTER Method which will be designed using Visual Basic 2008 and using MySQL. In the Visual Basic design, a calculation and ranking process will be produced